120k views
4 votes
F(x) = x 4x + 6g(x) = 3.x = 1Find: (gºf)(x)

F(x) = x 4x + 6g(x) = 3.x = 1Find: (gºf)(x)-example-1
User DrinkBird
by
4.9k points

1 Answer

5 votes

Consider the given functions,


\begin{gathered} f(x)=x^2-4x+6 \\ g(x)=-3x+1 \end{gathered}

Solve for the composite function as follows,


\begin{gathered} g\circ f(x) \\ =g\mleft(f\mleft(x\mright)\mright) \\ =g\mleft(x^2-4x+6\mright) \\ =-3(x^2-4x+6)+1 \\ =-3x^2+12x-18+1 \\ =-3x^2+12x-17 \end{gathered}

Thus, the required composit function is obtained as,


g\circ f(x)=-3x^2+12x-17

User Sunitkatkar
by
5.3k points